2019
DOI: 10.36709/jte.v4i4.13971
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Conjunction in Students’ Writing Recount Text at Second Grade of Sman 1 Tongkuno

Abstract: This research aims to investigate the types of conjunctions and the accurately use of conjunction in students’ writing. This research was conducted in SMAN 1 Tongkuno. The instrument of this research was students’ writing that focused on recount text. This research employed descriptive qualitative design. The population of this research was the second-grade students of SMAN 1 Tongkuno. The sample of this  research  is  the  second-grade  students of SMA N 1 Tongkuno consist of 20 students. The researcher colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…It is supported with the research by Andani & Miliha (2019) they found that the students are able to use all the types of conjunction such as additive, temporal, causal and adversative conjunction. The accuracy of conjunction used by students on their writing contribute highly to the quality of writing students.…”
Section: Discussionsupporting
confidence: 58%
“…It is supported with the research by Andani & Miliha (2019) they found that the students are able to use all the types of conjunction such as additive, temporal, causal and adversative conjunction. The accuracy of conjunction used by students on their writing contribute highly to the quality of writing students.…”
Section: Discussionsupporting
confidence: 58%
“…Selanjutnya, penelitian mengenai penggunaan konjungsi dan kesalahan penggunaan konjungsi di dalam tulisan siswa juga pernah diteliti oleh (Alfalagg, 2020;Andani et al, 2019;Batubara et al, 2021;Geraldine, 2018;Hamed, 2014;Yusti, 2022). Hasil penelitian tersebut menunjukkan adanya kekurangtepatan serta bentuk kesalahan penggunaan konjungsi di dalam berbagai jenis tulisan siswa.…”
Section: Pendahuluanunclassified